Visitors' satisfaction towards facilities at Gunung Lang Recreational Park, Perak - Wong, Poh Shyen (2018)
The study has been conducted at Gunung Lang Recreational Park (GLRP) due to the negative news reported regarding the facilities provided at the park have disappoint the visitors. GLRP is one of the recreational park located in the state of Perak and it has become a famous tourist destination in recent years. The main objective of this study is to determine the level of visitors' satisfaction towards facilities provided at GLRP. The socio-demographic characteristics and factors that affects visitors' satisfaction towards facilities have been studied. Questionnaire was used to collect data and 250 respondents were selected purposively. Data was analyzed using Descriptive Analysis and Multiple Linear Regression. The level of satisfaction was measured using Likert scale. Visitors overall satisfaction index towards the facilities provided at GLRP was 3.12 This indicates that visitors were less interested and consideration towards the facilities provided, which the existence of facilities is not the main concern of visitors. The condition of the wooden village houses obtained the highest mean score (3.66). The attractiveness of ticketing counter obtained the lowest mean score (2.55). Five significant factors affecting visitors' satisfaction level were identified through this study, which were visit companion, re-visit intention, marital status, ethnic and mode of transportation.